HIV infection in North African patients - (:unkn) unknown (My University, 2019)
North Africa is one of the rare regions where the HIV epidemic is growing. In France, 5% of the migrants discovering their HIV infection are from North Africa. The objective of this study was to compare the sociodemographic characteristics and outcomes of North African and French HIV-infected patients. This study was conducted in the HIV clinic of Bichat Hospital (Paris, France). The North African HIV-infected patients were born in Algeria, Tunisia, or Morocco or had lived there for more than 6 months. They were matched for age and gender (1:2) to patients born in France who had never lived outside France for more than 6 months. Sociodemographic, clinical, and immunovirological characteristics of North African and French patients were compared using conditional logistic regression. Among 4,738 eligible patients, 285 North Africans were identified. CD4 levels at HIV diagnosis were not significantly different between North African and French patients, but were more frequently <200/mm3 in the former than the latter at treatment initiation (p = .02). CDC stage 3 disease occurred more frequently in the first 3 years of care in our center in North African patients than in French patients (p = .01), and control of the HIV viral load over the 12 months preceding inclusion was better in French patients (p = .0001). There was no difference regarding loss to care. These results highlight possible issues in adherence to antiretroviral treatment in North African patients, which may be related to differences in the acceptability of the disease.
Keywords: African Research